The Psychometric Properties of the Norwegian version of CRAFFT Screening Test - Rye, Marte; Kopasov, Roman A. (PsykTestBarn, 2020)
CRAFFT was originally developed by Knight et al. (1999) as a brief screening instrument to identify adolescents at risk for alcohol and drug misuse. The instrument is copyright protected by the Boston Children’s Hospital. This article examines two Norwegian translations but no information on the translation processes is available. The instrument consists of six items identified by the acronym CRAFFT (Car, Relax, Alone, Forget, Friends, Trouble). There are no formal requirements of competence for administration and interpretation of scores. The literature search resulted in ten included articles, nine of which were Norwegian articles and one that was Swedish. The articles came from four studies. Together, the studies presented data from adolescence in the age group 15-19 years. Seven articles came from different subsamples from the longitudinal studies ung@hordaland and Barn i Bergen (N = 7874 – 9705), while one study came solely from the Barn i Bergen study (N = 2438). One article was based on a twin study including 717 pairs of twins, while the last study was a Swedish cross-sectional study consisting of a general population sample (n = 1443) and a sample of treatment seeking youth (n = 59). Three articles presented mean values and standard deviations for the CRAFFT total score. Seven articles reported the prevalence of problematic alcohol and drug use for different subsamples as measured by CRAFFT with cut-off score ≥ 2. Seven articles reported reliability estimates. Two articles reported construct validity, while concurrent validity, sensitivity and specificity were reported in two articles. The ten included articles support that CRAFFT has satisfactory psychometric properties. As seven of the articles originate from the same study, it is desirable for future research that the instrument be studied in other samples in terms of, for example, geographical location and age groups. This is to further strengthen the instrument`s psychometric properties and examine if findings generalize across different samples.